Description of longitudinal cranial imaging and cognitive changes in the Strong Heart Study: Epidemiology / Prevalence, incidence, and outcomes of MCI and dementia. (7th December 2020) - Suchy‐Dicey, Astrid M; Verney, Steven P; Nelson, Lonnie A; Grabowski, Thomas J; Buchwald, Dedra
Abstract: Background: Little is known about cognitive impairment and dementia in American Indians, who are underrepresented in most studies of Alzheimer's disease and related dementias. Method: The Strong Heart Study recruited 4, 549 American Indians aged 45‐75 from 3 major geographic regions in 1989‐1991. In 2010‐2013 and again in 2017‐2019, all eligible surviving participants were recruited for comprehensive cranial magnetic resonance imaging, cognitive, and clinical examinations. Neurological data collected included history of stroke and neurological symptoms. Cognitive data included Modified Mini Mental Status Examination, Weschler Adult Intelligence Scale, Controlled Word Association Test, California Verbal Learning Test, Wide Range Achievement Test, Montreal Cognitive Assessment, Craft Story Recall, Benson Figure Copy, Number Span test, Category Fluency, Trail Making test, Multilingual Naming Test, Functional Activities Questionnaire. Physical function tests included Short Physical Performance Battery, dynamometric grip strength, and Halstead finger tapping test. Mood and quality of life tests included Short Form 36 and Centers for Epidemiologic Studies Depression scale. Clinical examination included anthropometric measures, blood pressure, and basic blood and urine laboratory assays including serum glucose, lipids, creatinine, and albumin. Neuroradiologists blinded to clinical data examined MRI for vascular and structural findings, including presence and location of infarcts, hemorrhages, white matter hyperintensities, sulcal widening, ventricle enlargement, and volumetric estimates of hippocampus, parahippocampal gyrus, thalamus, and frontal lobe. Neuropsychologist panels adjudicated cognitive impairment and dementia by case review. Result: This report describes the structure and methods used to collect these longitudinal data, including the cognitive examinations, the neuropsychological data cleaning, and the panel‐based case reviews. We also include basic epidemiologic description of the data, including changes in cranial imaging findings and cognitive and functional examinations between the two neurological examinations (approximate follow‐up time: 7 years). Conclusion: This report adds to existing literature with the first longitudinal description of cranial imaging and cognitive testing data in American Indian elders, as well as the first cognitive measurements related to Alzheimer's disease, in this population. These data may be used to estimate incidence and prevalence of vascular brain injury, structural atrophy, imaging markers related to Alzheimer's disease, and cognitive function in this understudied population.